ANALISIS PERAN DEPARTEMEN SUMBER DAYA MANUSIA PADA PERUSAHAAN X DI KOTA BANDUNG - Erna Resmiatini; Ratri Wahyuningtyas (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2013)
X Company implement several strategies to win the competition through increasing human resources ability and creativity. The condition in X company that there haven’t human resources (HR) department for 20 years. After realized that HR department is very important in every company, HR department has been established in 2010. For maximizing it’s job, HR department in X company need to know the level of implementation HR department roles. Based on theory from Ulrich and Brockbank (2005), HR department roles are consist of Employee Advocate, Human Capital Developer, Functional Expert, Strategic Partner and HR Leader. The purposes of this research are to know the level of implementation HR department roles ini X company based on theory from Ulrich and Brockbank (2005) and also want to know the domination of HR department roles. Research type is descriptive quantitative. Method of analysis are descriptive analysis and confirmatory factor analysis with LISREL versi 8.8 software. Result from this research show that HR department in X company has implemented HR department roles with high category. Among the five factors as forming of HR department roles, Fuctional expert more dominant than Employee Advocate, Human Capital Developer, Strategic Partner dan HR Leader. Key words : HR department roles, Employee Advocate, Human Capital Developer, Functional Expert, Strategic Partner dan HR Leader